ANALISIS PENGARUH DESAIN LABEL KEMASAN SAUS TIRAM TERHADAP MINAT BELI KONSUMEN: ANALYSIS OF THE INFLUENCE OF OYSTER SAUCE PACKAGING LABEL DESIGN ON CONSUMER BUYING INTEREST - Andri Arief Irdasyah; Elda Franzia Jasjfi; Achmad Syarief (Universitas Trisakti, 2026)
Analysis Of The Influence Of Oyster Sauce Packaging Label Design On Consumer Buying Interest. This research aims to analyze the influence of oyster sauce packaging label design on consumer purchasing interest. Packaging label design is considered an important factor in influencing consumer purchasing decisions because it has a significant role in attracting attention, conveying product information, and creating a perception of value. This research uses a quantitative and qualitative approach by collecting data through surveys of sample consumers, who are randomly selected from the relevant population. The collected data was analyzed using various statistical methods such as regression analysis to identify the relationship between variable packaging design elements (such as color, illustrations, typography and brand materials) and consumer purchasing interest. It is hoped that the findings from this research will provide useful insights for manufacturers in designing attractive packaging label designs and influencing consumer purchasing interest, so as to increase product competitiveness in the market. Apart from that, the results of this research can also be a basis for further research to deepen understanding of the influence of packaging design on consumer behavior.